The effect of resistance training combined with ingestion of protein drinks on muscle fibre size and muscle strength - Andersen, L. L.; Tufekovic, G.; Zebis, M. K.; Crameri, R.; Verlaan, G.; Kjaer, M.; Suetta, C.; Magnusson, P.; Aagaard, P. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Acute muscle protein metabolism is modulated not only by resistance exercise but also by amino acids (Tipton et al., 2001). However, less is known about the long-term hypertrophic effect of protein supplementation in combination with resistance training (Esmarck et al., 2001). The present study was designed to compare the effect of 14 wks of resistance training combined with timed ingestion of iso-caloric protein vs. carbohydrate supplementation on muscle fiber hypertrophy and mechanical muscle performance. Methods 22 moderately physically active males (23.2 ± 0.6 years, 184.5 ± 2.0 cm, 77.0 ± 2.6 kg) participated in the study. 25 g of supplementation was administered prior to and immediately after each training bout, and in addition in the morning on non-training days. Pre- and post-training muscle biopsies were obtained from the vastus lateralis muscle and analyzed for muscle fiber cross-sectional area (fCSA). Squat jump (SJ) and countermovement jump (CMJ) were performed on a force platform to determine vertical jump height. Peak torque during slow (30°s-1) and fast (240°s-1) concentric and eccentric contraction of the knee extensor muscle was measured in an isokinetic dynamometer. Two-way ANOVA were used for statistical analysis. Results After 14 wks resistance training the protein group showed hypertrophy of type I (18 ± 5 %, p<0.01) and type II (26 ± 5 %, p<0.01) muscle fibers, whereas no change above baseline occurred in the carbohydrate group (Fig. 1). SJ height increased only in the protein group (9 ± 2 %, p<0.01), whereas CMJ height and peak torque during slow isokinetic muscle contraction increased similarly in both groups. Discussion The present results demonstrate that resistance training combined with timed protein ingestion, but not carbohydrate ingestion, is effective in inducing muscle fiber hypertrophy in young healthy males. These results are in line with previous studies on acute muscle protein metabolism (Tipton et al., 2001) as well as a long-term resistance training study in the elderly (Esmarck et al., 2001). Furthermore, some indications of a beneficial effect of protein over carbohydrate supplementation were seen on the functional muscle test.